Optimalisasi pH pada Waste Water Treatment Limbah Pengolahan Pelumas Bekas Dengan Analisa COD, BOD, TSS, dan NH3 - Mudhofar, M syaifudin zuhdi; Abrina Anggraini , Sinar Perbawani; Widyastuti, Fikka Kartika (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Rapid development occurs in the industrial sector. However, not many industries pay attention to the aspect of environmental pollution. There is a need for a higher quality handling of industrial waste disposal, by determining the standard quality of industrial liquid waste disposal including pH, COD, BOD, TSS, NH3. Ph optimization is one way that can be used to obtain better quality standards, of course, to reduce the contamination levels of COD, BOD, TSS, NH3 in this study using analysis from DIN38409 / 52, ASTM 1252, HACH 8006, and ASTM D. 1068 B. The results identified the optimal pH of used lubricating waste water purification in the analysis of BOD, COD, TSS, and NH3, namely at ph 7. with the highest percentage reduction in contamination levels from COD 97.76%, BOD 98.46%, TSS 88 , 40%, and NH3 94.32%.